Parents as first Teachers for Children - Rosalia Windu Asih (Universitas Sebelas Maret, 2020)
Parents are the firs environment a child experiences when he is born into the world.Furthermore,parents are also the main environment in shaping a child’s personality.At the beginning of their growth, they tend to spend more with the family environment,especially parents.Then in the family a child experiences the first and foremost educational process of the parents.All forms of parental behaviour,both oral and good deeds that are exemplary and habits applied in social life wiil affect the pattern of child development.Therefore,my parents should able to instill a good education and of course this is true in children from an early age,so that the subsequent development of children can reflect a good and noble personality as well as be beneficial for themselves ,parentsriligion,society and nation and country.